Lusophony : communication in the portuguese speaking world - Sousa, Helena (1999)
This article provides a general overview of media and communication in the Portuguese Speaking World. It could be said that the media were an awareness catalyst for Lusophone issues well before the formal constitution of the Lusophone Community. Even in periods of more tense political/diplomatic relations between Lusophone countries, the media always maintained what could be described as a minimum connection. Information has traditionally circulated with ease in this space through news agencies, newspapers, radio and television international broadcasts. Films, series, sports programmes, and cultural products such as telenovelas, faced no cultural resistance, being well received in all Lusophone countries. Brazil and Portugal clearly are the main producers of information and entertainment content but the content flow is far from being unidirectional.